Culturally Sustaining Leadership: A Pacific Islander's Perspective - Mary Therese Perez Hattori (MDPI AG, 2016)
Social justice in educational settings can be advanced through culturally sustaining leadership development programs for indigenous students, faculty, and administrators. The state of Hawai'i has been a fertile ground for culture-based development experiences for emerging leaders from islands throughout the Pacific. These opportunities arise from the recognition of dissonance created by customary leadership programs which often give little or no attention to native cultures of the Pacific islands and prioritize other models. This essay highlights elements of my Chamoru culture that form the foundation of a culturally responsive leadership praxis within the context of American educational institutions. I offer this as an example that may help others develop their own culturally sustaining practices and inspire creation of leadership development programs which honor native cultures while facilitating effective professional practices in mainstream settings.